Molecular epidemiology and drug resistance of Mycobacterium tuberculosis in a tertiary care hospital in northeastern Mexico - Flores-Aréchiga, Amador; Zacarías-Hernández, José Luis; Vázquez-Cortés, Cecilia Gabriela; Tamez-Guerra, Reyes S; de la O-Cavazos, Manuel; Rivera-Morales, Lydia Guadalupe; Llaca-Díaz, Jorge Martín; Castro-Garza, Jorge; Casillas-Vega, Néstor; Vázquez-Guillén, José Manuel; Rodríguez-Padilla, Cristina (The Journal of Infection in Developing Countries, 2023)
Introduction: Tuberculosis (TB) is a re-emerging disease considered a public health concern. In the present study, we analyzed the epidemiology and drug resistance of Mycobacterium tuberculosis strains isolated from patients with pulmonary TB. Methodology: Mycobacterium tuberculosis isolates (n = 190) were obtained from patients with pulmonary TB admitted to Dr. José Eleuterio González University Hospital (UH). Each M. tuberculosis isolate was analyzed by spoligotyping (spacer oligonucleotide typing) and MIRU-VNTR (Mycobacterial Interspersed Repetitive Units-Variable Number Tandem Repeat). Drug resistance was evaluated using the Anyplex™ II MTB/MDR/XDR assay. Results: The predominant spoligotypes observed were X1 (SIT 119, n = 46), T1 (SIT 53, n = 40), H3 (SIT 50, n = 13), Beijing (SIT 1, n = 11), and EAI2-Manila (SIT 19, n = 8). MIRU-VNTR analysis showed that the locus QUB-26 had the highest allelic variability. The observed drug resistance included monoresistance to rifampicin (2.6%; n = 5), isoniazid (3.2%; n = 6), and fluoroquinolones (1.6%; n = 3) as well as multidrug resistance (5.3%; n = 10). All of the Beijing strains were susceptible. Regarding comorbidities, 13.7% (26/190) of the patients were co-infected with TB and HIV (TB+HIV+), and 31.6% (55/190) had TB along with diabetes (TB + diabetes). Conclusions: The most prevalent lineages were X1 (SIT 119; 24.3%) and T1 (SIT 53; 21%). An alarming proportion (12.6%) of M. tuberculosis isolates presented drug resistance. To effectively manage TB, continuous surveillance of regional strain dissemination, drug resistance profiles, and TB-associated comorbidities is crucial.